Development of human neck numerical model for crashworthiness assessment - Azizan Fahmi, Mohamad (Universiti Malaysia Perlis (UniMAP), 2012)
Despite the recent progresses in occupant safety, protection of children is not still optimal. To offer a better understanding of child injury mechanisms, the present study proposes a dummy finite element model of newborn child neck. The neck model consists of rigid, geometrically accurate vertebrae held together with intervertibral disk, facet joints and ligaments modeled as a series of nonlinear springs. Neck injury that occurred in vehicle crash accident will be simulated using finite element analysis software, LS-DYNA and compared with other experimental results. In the case of a frontal impact, in the areas of neck compression, neck extension and neck kinematics, it is demonstrated that a good correlation is achieved between the response of a FE dummy in the model and those of ATDs in the physical hardware tests. As a reference in modeling, the new-born child dummy model a 50th percentile Hybrid III will be used. The geometry of the human neck will be adjusted and modified according to typical Malay new-born child.